1986
DOI: 10.1152/ajprenal.1986.250.2.f322
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic stimulation of the hypothalamus and natriuresis in rats: role of the renal nerves

Abstract: The role of the renal nerves in the natriuresis seen after cholinergic stimulation of the hypothalamus was studied in anesthetized rats treated with injection into the lateral hypothalamus (LH) of 1 microgram of carbamylcholine chloride (carbachol) in 1 microliter of 0.15 M NaCl or NaCl alone. Injection of carbachol exhibited diuresis and natriuresis both in acutely denervated kidneys (P less than 0.01) and in contralateral innervated kidneys (P less than 0.01) without changes in glomerular filtration rate (GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The denervation was accomplished by cutting all visible nerves along the renal artery and by stripping both renal artery and hilum of all nerve bundles. Immediately thereafter, the renal artery was surrounded with a cotton pledget that had absorbed a 1o (vol/vol) phenol solution in absolute ethanol (36)(37)(38) Carotid-aortic deafferented rats (n = 8) had significantly lower (P < 0.001) plasma ANP concentrations under basal conditions than the sham-operated rats (n = 7) (Fig. 1) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The denervation was accomplished by cutting all visible nerves along the renal artery and by stripping both renal artery and hilum of all nerve bundles. Immediately thereafter, the renal artery was surrounded with a cotton pledget that had absorbed a 1o (vol/vol) phenol solution in absolute ethanol (36)(37)(38) Carotid-aortic deafferented rats (n = 8) had significantly lower (P < 0.001) plasma ANP concentrations under basal conditions than the sham-operated rats (n = 7) (Fig. 1) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These effects are only partially due to the release of neurohypophysial hormones, since the administration of OT and AVP promoted a further effect of LHA stimulation (479). Silva-Netto et al (478) have also shown the natriuretic effect of carbachol stimulation of the LHA in rats with intact or denervated kidneys. The control values for Na ϩ excretion were significantly higher in rats with denervated kidneys, consistent with the previously described "denervation diuresis" (114, 115, 119).…”
Section: Role Of ␣-Adrenergic and Cholinergic Receptors In Controlmentioning
confidence: 98%
“…In addition, other authors have demonstrated that the central injection of carbachol in duces a natriuretic response that is not me diated by a rise in arterial pressure [9]. These authors have presented evidence that a hor monal factor is responsible for the increase in sodium excretion, at least with hypotha lamic injections [10].…”
Section: Discussionmentioning
confidence: 98%